Perceptions of Nigerian medical students regarding their preparedness for precision medicine: a cross-sectional survey in Lagos, Nigeria - Ogamba, CF; Roberts, AA; Ajudua, SC; Akinwale, MO; Jeje, FM; Ibe, FO; Afolayan, MM; Kuyinu, YA (BioMed Central, 2023)
Background Advances in precision medicine in Nigeria suggest improving genomics education and competency among healthcare practitioners to facilitate clinical translation. Due to the scarcity of research in this area, this study aimed to assess Nigerian medical students’ perceptions about their preparedness to integrate precision medicine into their future clinical practice.